Ansiedad y rendimiento académico en estudiantes de educación general básica de la Unidad Educativa “Riobamba”. Riobamba. 2016-2017 - Salcedo Vite, David Antonio (2017)
The present research addressed the theme “Anxiety and Academic Performance in Students of Basic Education of the Educational Unit Riobamba”, is an issue that takes great importance considering that multiple social changes alter the bio-psycho-social balance of individuals and especially of the study population, which is in the stage of childhood, which must be attended and advised with responsibility, since it is the basis for personal development; This study was designed to identify anxiety levels, to analyze academic performance and to relate them. Lang's anxiety is a response given by the subject to situations he perceives or interprets as threats or dangers. We worked with a non-experimental qualitative design, the Deductive-Inductive and Analytic-Synthetic methods were considered; the type of research was diagnostic and exploratory. The population consisted of 112 students. The Jhon Gillis Anxiety Test was structured by 20 dichotomous questions. After analysis and interpretation of data it is concluded that the outstanding anxiety levels are mild, relaxation and severe, most students are within the qualitative scale of academic achievement "reaches the required learning"; Within the levels of moderate and severe anxiety, it was found that the highest percentage of the population that is located in the mentioned scale, which indicates that the anxiety does influence in the academic performance, since, it makes it difficult for the students to position themselves in scales Qualitative tests.